Influence of COVID-19 pandemic on dissemination of innovative e-learning tools in higher education in Poland - Kinga Stecuła; Radosław Wolniak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The paper presents the results of the research on the influence of the COVID-19 pandemic on the dissemination of innovative e-learning tools in higher education. Research was carried out in Poland in December 2021 on a sample of 621 students. The main issue that was the subject of the author's analysis was the influence of the COVID-19 pandemic on the change in the use of innovative e-learning tools in university education. After conducting the research and discussing this and related research about e-learning during the pandemic, it was concluded that the percentage of students familiar with the analyzed e-learning tools has increased significantly during the pandemic. There has been a visible rise, especially in the usage of the following tools: MS Teams, Zoom, and Google Classroom. The most frequently used e-learning tools during the COVID-19 pandemic have been mainly videoconferencing tools such as MS Teams and Zoom. However, students also have used e-learning platforms and e-mails. The author's research identified three hidden factors (categories) of the used e-learning tools. They include the following categories: popular services and applications adapted to e-learning; popular applications for synchronous meetings adapted to e-learning; and other synchronous and asynchronous e-learning methods. The familiarity with information technology, as well as an interest in innovative e-learning tools, have positive influence on the ease of acquiring content in e-learning. Having the proper resources also positively influences the absorption of e-learning content. On the basis of the achieved results, the authors prepared a model of relations between students' interest in innovative e-learning technology and the resources they possess to participate in e-learning classes. This model enables us to assess which method-e-learning, traditional or hybrid-should be used in the given situation. The developed model can be useful for universities. They can assess the students' interest in innovative e-learning technologies and their level of technical resources using questionnaires and on this basis divide students into groups to prepare the optimal learning way-e-learning, traditional or hybrid.
Keywords: 650; COVID-19 pandemic; e-learning; innovation; innovative education; synchronic education; traditional education